2007
DOI: 10.1002/hipo.20349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise on NMDA receptor subunit contributions to bidirectional synaptic plasticity in the mouse dentate gyrus

Abstract: We examined synaptic plasticity in the dentate gyrus (DG) of the hippocampus in vitro in juvenile C57Bl6 mice (28-40 days of age), housed in control conditions with minimal enrichment (Controls) or with access to an exercise wheel (Runners). LTP expression was significantly greater in slices from Runners than in those from Controls, but could be blocked by APV in both groups. LTP was significantly reduced by NR2B subunit antagonists in both groups. NVP-AAM077, an antagonist with a higher preference for NR2A su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 45 publications
(69 reference statements)
2
74
0
1
Order By: Relevance
“…NMDA-dependent cellular mechanisms could also mediate the effects of running on consolidation of the fear memory, its extinction, and its reconsolidation. Consistent with this suggestion, exercise altered the contribution of NMDA NR2A subunits to synaptic plasticity in the dentate gyrus (Vasuta et al 2007). Administration of the NMDA receptor antagonist MK-801 was shown to reduce both the arterial pressure and heart rate increase evoked by dynamic exercise (Camargo et al 2013).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…NMDA-dependent cellular mechanisms could also mediate the effects of running on consolidation of the fear memory, its extinction, and its reconsolidation. Consistent with this suggestion, exercise altered the contribution of NMDA NR2A subunits to synaptic plasticity in the dentate gyrus (Vasuta et al 2007). Administration of the NMDA receptor antagonist MK-801 was shown to reduce both the arterial pressure and heart rate increase evoked by dynamic exercise (Camargo et al 2013).…”
Section: Discussionmentioning
confidence: 61%
“…Extinction learning involves a distributed network of brain areas centered around activity in the BLA, while consolidation recruits other circuits and brain areas (Herry et al 2010). Memory consolidation, extinction, and reconsolidation have been shown to be dependent on activation of glutamate NMDA receptors, and physical exercise may act to augment these mechanisms (Vasuta et al 2007). NMDA receptor antagonists have been demonstrated to disrupt the consolidation (Goeldner et al 2009;Charlier and Tirelli 2011), extinction (Falls et al 1992 (Lee et al 2006;Kalisch et al 2009;Yamada et al 2009) and facilitate extinction (Walker et al 2002;Ledgerwood et al 2003;Vervliet 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies support the enhancement effects of exercise on LTP only at the dentate gyrus (DG) but not the CA1 synapses in wild-type animals with normal health conditions (van Praag et al 1999;Vasuta et al 2007). However, physical training can revert the reduced CA1 LTP in rodents following disturbance such as epilepsy or sleep deprivation (Arida et al 2004;Zagaar et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The glutamate receptor, NMDA, is involved in activity-dependent synaptic plasticity, including long-term potentiation (41). It was identified that exercise is a necessary step for initiating activity of the NMDA receptor in the hippocampus (42) and that exercise-enhanced NMDA receptor expression promotes postnatal motor-unit maturation in a spinal muscular atrophy mouse model (43).…”
Section: Discussionmentioning
confidence: 99%